2006
DOI: 10.2135/cropsci2005.0056
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Fiber and Yield QTLs with Main, Epistatic, and QTL × Environment Interaction Effects in Recombinant Inbred Lines of Upland Cotton

Abstract: Most agronomic traits of cotton (Gossypium hirsutum L.) are quantitatively inherited and affected by environment. The importance of epistasis as the genetic basis for complex traits has been reported in many crops. In this study, a linkage map was constructed by means of a recombinant inbred line (RIL) population derived from 72353TM-1. Main effects, epistatic effects, and environmental interaction effects of quantitative trait loci (QTLs) controlling fiber and yield component traits were determined by mixed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 30 publications
2
63
0
1
Order By: Relevance
“…Earlier, we identified several loci controlling SSC in soybean (Dhungana et al 2017) and observed that majority of the QTL for SSC were found to be significantly influenced by the growing environment. Such effects have been observed for other complex traits like forage quality (Asekova et al 2016), isoflavone content (Primomo et al 2005), seed weight , seed protein (Panthee et al 2005), fatty acid composition, oil and protein contents (Rennie and Tanner 1989;Dornbos and Mullen 1992;Primomo et al 2002;Fehr et al 2003;Hou et al 2006;Oliva et al 2006;Dhakal et al 2013;Asekova et al 2014), and yield (Rao et al 2002;Shen et al 2006) in soybean.…”
Section: Introductionmentioning
confidence: 93%
“…Earlier, we identified several loci controlling SSC in soybean (Dhungana et al 2017) and observed that majority of the QTL for SSC were found to be significantly influenced by the growing environment. Such effects have been observed for other complex traits like forage quality (Asekova et al 2016), isoflavone content (Primomo et al 2005), seed weight , seed protein (Panthee et al 2005), fatty acid composition, oil and protein contents (Rennie and Tanner 1989;Dornbos and Mullen 1992;Primomo et al 2002;Fehr et al 2003;Hou et al 2006;Oliva et al 2006;Dhakal et al 2013;Asekova et al 2014), and yield (Rao et al 2002;Shen et al 2006) in soybean.…”
Section: Introductionmentioning
confidence: 93%
“…Cottonseed protein cake and oil are secondary products and have been drawing a large interest as animal feed (Arieli 1998), human consumption (O'Brien and Wakelyn 2005), and biodiesel feedstock (Royon et al 2007). With the advent of molecular marker technology, it became possible to construct saturated genetic maps (Rong et al 2004;Guo et al 2007) and to locate QTL for lint yield (Shen et al 2006b;He et al 2007), fiber quality (Paterson et al 2003;Lacape et al 2005;Park et al 2005), seed traits , and response to biotic or abiotic stress (Wright et al 1998;Saranga et al 2004;Shen et al 2006a) to linkage groups or chromosomes in cotton. However, limited information is known about the direct association or interaction among specific genes and the variations of traits of interest such as cotton fiber (Ruan et al 2003;Arpat et al 2004;Lee et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, indirect selection in breeding is also difficult in breeding practice because of neglect in the correlation among non-target traits and the lack of an effective method with which to unify the same genetic effects of different traits (Galanopoulou-Sendouca and Roupakias 1999; Mccarty et al 2008). Modern molecular biology and quantitative genetics reveal that QTL has various effects, such as additive and dominance effects, among others (Shen et al 2006;Jiao et al 2010). Its complex correlativity makes the genetic relationship among characters much more difficult to Table 8 Decision-making coefficients (R i ) of the genetic components of other characters to fiber length, strength, and micronaire individual and order from maximum to minimum for R select than non-target traits.…”
Section: Discussionmentioning
confidence: 99%